Formation of the male-specific muscle in female Drosophila by ectopic fruitless expression. - Usui-Aoki, K.; Ito, H.; Ui-Tei, K.; Takahashi, K.; Lukacsovich, T.; Awano, W.; Nakata, H.; Piao, Z.F.; Nilsson, E.E.; Tomida, J.; Yamamoto, D. (Nature Cell Biology, 2000)
The Drosophila fruitless (fru) gene product Fru has been postulated to be a neural sex-determination factor that directs the development of at least two male-specific characteristics, namely courtship behaviour and formation of the muscle of Lawrence (MOL). The fru gene encodes a putative transcription factor with a BTB domain and two zinc-finger motifs, and with consensus Tra-binding sequences. The binding of Tra to these sequences results in sex-specific alternative splicing of the fru mRNA, leading to production of the 'male-type' or 'female-type' Fru protein. We show here that the Fru protein is not detected in the female central nervous system (CNS), despite the similar level of expression of fru mRNA in both male and female CNS. As ectopic expression of both the 'male-type' (with the sequence for the amino-terminal extension) and 'female-type' (without the sequence for the amino-terminal extension) fru cDNA can induce formation of the MOL in females, the presence or absence of the Fru protein, and not its sex-specific structure, seems to be responsible for the sexually dimorphic actions of the fru gene.